Gender differences in juvenile systemic sclerosis patients: Results from the international juvenile scleroderma inception cohort - Foeldvari, Ivan; Klotsche, Jens; Kasapcopur, Ozgur; Adrovic, Amra; Terreri, Maria Teresa; Sakamoto, Ana Paula; Stanevicha, Valda; Anton, Jordi; Feldman, Brian M; Sztajnbok, Flavio; Khubchandani, Raju; Alexeeva, Ekaterina; et al. (Journal of scleroderma and related disorders, 2023)
OBJECTIVE: To compare organ involvement and disease severity between male and female patients with juvenile onset systemic sclerosis. METHODS: Demographics, organ involvement, laboratory evaluation, patient-reported outcomes and physician assessment variables were compared between male and female juvenile onset systemic sclerosis patients enrolled in the prospective international juvenile systemic sclerosis cohort at their baseline visit and after 12 months. RESULTS: One hundred and seventy-five juvenile onset systemic sclerosis patients were evaluated, 142 females and 33 males. Race, age of onset, disease duration, and disease subtypes (70% diffuse cutaneous) were similar between males and females. Active digital ulceration, very low body mass index, and tendon friction rubs were significantly more frequent in males. Physician global assessment of disease severity and digital ulcer activity was significantly higher in males. Composite pulmonary involvement was also more frequent in males, though not statistically significantly. After 12 months, they are the pattern of differences changed female patients had significantly more frequent pulmonary involvement. CONCLUSION: In this cohort, juvenile onset systemic sclerosis had a more severe course in males at baseline and but the pattern changed after 12 months. Some differences from adult findings persisted, there is no increased signal of pulmonary arterial hypertension or heart failure in male pediatric patients. While monitoring protocols of organ involvement in juvenile onset systemic sclerosis need to be identical for males and females.
Keywords: clinical characteristics; juvenile systemic sclerosis; male; gender; Scleroderma; disease severity